Some Performance Analysis Applications of Stochastic Modeling - Horváth Ádám (2014)
Models which have been used for a long time to understand and analyze processes, try to capture the essence of problems, and – as far as possible – simply describe the operation of these processes. In this dissertation, we deal with two main topics. First, we investigate the spreading of services (applications), model the spreading process, and evaluate the models. Then, we propose a model for modeling the opportunistic spectrum access and analyzing its effects. Nowadays, mobile applications became even more popular with the proliferation of smart phones. Applications can be purchased usually through a web shop. However, there exist decentralized technologies like self-organized or ad hoc networks, in which users can download and try out applications directly from each other (secure payment in this environment is still a challenging issue today, therefore, direct application download concerns only the trial versions of the applications). The possibility of trying out an application can give additional motivation to purchase it. Moreover, there are other advantages like the community experience in case of a multi-player game. This approach can better motivate the users to purchase an application than they would have seen only some advertisements. Since one of the goals in this work is to point out the relation of this area and the wood industry, we also modeled the production process of a company producing wooden windows. Using the model, the leaders of the company can find answers for questions like determining the bottleneck in the producing process. Our other topic is also a novel one. However, the basic idea of the opportunistic spectrum access is not a novelty. Nowadays, it is widely recognized that spectrum management reform and dynamic spectrum access can provide a solution to an existing problem (the shortage of usable radio frequencies and the under-utilization of the licensed spectrum), the application of dynamic and opportunistic spectrum access is rarely found in practice. A lot of issues must be solved before the widespread application of opportunistic spectrum access. Amongst these issues, a question concerning the investment (on the licensed frequencies and technology) protection of the incumbent operators plays an important role regarding the acceptance of opportunistic spectrum access. In both areas, we made an effort to reconsider the inflexible structure of the existing approaches and give alternative solutions for the main questions of the investigated topics. In the first part of the dissertation, we investigate the mobile application spreading. In the proposed model, the application spreading process is based on the direct (ad hoc) communication between the users. In case of the mobile cellular networks, we can observe also an inflexible structure: the service providers can get exclusive right to certain frequency bands on auctions held by the government. The exclusiveness involves the bad utilization of the means, although utilization becomes a key factor with the increasing demand for the bandwidth in this area. In the second part of the dissertation, we propose the introduction of the opportunistic spectrum access.